(untitled) (Journal of Psychiatrists’ Association of Nepal, 2022)
Introduction: Psychosocial problems are highly prevalent problems among children and adolescents and can severely interfere with their everyday functioning. It is crucial to raise awareness around mental health to reduce the negative beliefs and attitudes and provide professional help. This study is aimed to find out the level of awareness regarding suicide among adolescents. Material and Methods: A cross-sectional study was conducted to find out awareness regarding suicide among 300 adolescents in a school of Rupandehi district by using enumerative technique. Pretested, validated by experts and self-administered structured questionnaire was used to collect the data and collected data were analyzed by using descriptive and inferential statistics with SPSS-16. Results: The findings of the study revealed that among 300 respondents, 47.5% had high awareness regarding suicide. Respondents have high awareness regarding meaning, risk groups, consequences and immediate management of suicide but have low awareness regarding risk factors, methods, warning signs, prevention and long term management of suicide. Conclusion: Based on the findings of the study, it is concluded that nearly half of the respondents have high awareness regarding suicide. Suicide has been recognized as a major public health priority and advocate for the development and implementation of comprehensive strategies, taking into special consideration youth and other vulnerable groups. It is necessary to conduct awareness program on suicide to increase awareness among adolescents.